PENERAPAN USER CENTERED DESIGN (UCD) PADA WIREFRAME DESAIN USER INTERFACE DAN USER EXPERIENCE APLIKASI SINOPSIS FILM - Muhammad Syarif Hartawan (Institut Teknologi dan Bisnis Swadharma, 2022)
The purpose of this research is as a prototype for the application of User Centered Design in the development of User Interface Design and User Experience on the Film Synopsis android application. In developing android applications, the design of the User Interface (UI) and User Experience (UX) is a very important initial stage in using the application. This UI/UX will provide a user experience in using and interacting with this android application. In this article, we explain how UI/UX is designed in Film Synopsis using a User Centered Design (UCD) approach. At UCD there are 4 (four) stages in the UI/UX approach, namely analysis, design, evaluation, and implementation. Users will be involved in evaluating the designs that are made, so that the designs that are formed (made) can be improved for the convenience of users or android application users